Sosialisasi Optimalisasi Potensi Limbah Organik Rumah Tangga dengan Mengaplikasikan Lubang Resapan Biopori dalam Penanaman Tanaman Buah: Socialization on Optimizing the Potential for Household Organic Waste by Applying the Biopore Hole in Planting Fruit Plants - Anshory, Jamil; Ramadhani, Muhammad Nur; Riyadi, Aldi Wibawan; Hadyanto, Rafi Firmana; Indasari; Pangestu, Muhammad Rafif; Rombe, Sang A. P. Raysha; Sanjaya, Rico Arswendo; Nong, Angela Stevania; Ananda, Dita; Musdalifah, Siti; Rahmarezkya, Nurlaila; Austina, Karmelita (Jurnal ETAM, 2024)
Kelurahan Buluminung is one of the villages in Penajam Sub-district, Penajam Paser Utara Regency. This village has several problems, one of which is the absence of temporary shelters (TPS) and final processing sites in the Muan area (RT 2 to RT 6). The purpose of this activity is to overcome organic waste that is easily degraded by applying biopore infiltration holes in planting fruit plants. The method used in this activity is divided into two, namely direct practice in the field (applied) and socialization. The applied part consists of several stages, namely the layout of land facilities, soil pH measurement, making biopore infiltration holes, selecting fruit plant seeds, planting fruit plants, and installing SOPs for the utilization of biopore infiltration holes. After that, socialization was carried out to show the results of practice directly in the field. This socialization activity was divided into three main materials, namely 1) Biopori, 2) Fruit Planting, and 3) Fruit Plant Care. The results obtained from this activity are the implementation of direct practice in the field and socialization of the use of biopore infiltration holes in planting fruit plants in the general public of Buluminung village. There were people who managed to make biopore infiltration holes and apply them in their yard after the implementation of this activity.